Intelligence Report on Ngi Clan Bamenda Division (Colonial Letters and the Contact of Knowledges, 1935)
This file contains colonial proposal, inspection note and progress report including map
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies